Penerapan Konsep Arsitektur Vitruvius dalam Desain Kontemporer Fasad Rumah Tempat Tinggal : Studi Kasus Rumah Tempat Tinggal Denny - Rahmat Setiawan; Ulinnuha Khoirul Rizal (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Denny's house is one of the houses that uses a minimalist architectural concept. The minimalist concept has become a trend in the world of architecture, because of its simple yet effective concept, minimalist design has become one of the most preferred styles by graphic design professionals, architects, and artists (Aliwafa, 2023). The actualization of the Vitruvius architectural concept is based on Vitruvius's theory of Utility (Function Aspect), Firmitas (Strongness and Structure Aspect), and Venustas (Beauty). By comparing Vitruvius's theory with Henry Wotton's Theory, the aim is to actualize the architectural concept in the contemporary design of Denny's house as well as become a case study that can be accepted by the reader's audience. This case study uses descriptive qualitative techniques of data processing that aim to achieve study results on a comprehensive phenomenon. The application of the Vitruvius architectural concept is the focus of discussion in the contemporary design of the facade of Denny's house which becomes a reference for the discussion to examine with an architectural approach. The house becomes the initial locus of discussion by prioritizing the function of beauty, the function of strength or structure, and the function of venustas or beauty. Vitruvius is a theory used to examine the application of design theory by providing a precedent study of Denny's architectural work, which uses a minimalist functionalist theme. This study examines Vitruvius' theory regarding the relevance of design to Denny's home.